Artificial Intelligence in Higher Education: A Bibliometric Study on its Impact in the Scientific Literature - Francisco-Javier; Inmaculada Aznar-Díaz; María-Pilar C; José-María (MDPI AG, 2019)
Artificial intelligence has experienced major developments in recent years and represents an emerging technology that will revolutionize the ways in which human beings live. This technology is already being introduced in the field of higher education, although many teachers are unaware of its scope and, above all, of what it consists of. Therefore, the purpose of this paper was to analyse the scientific production on artificial intelligence in higher education indexed in Web of Science and Scopus databases during 2007–2017. A bespoke methodology of bibliometric studies was used in the most relevant databases in social science. The sample was composed of 132 papers in total. From the results obtained, it was observed that there is a worldwide interest in the topic and that the literature on this subject is just at an incipient stage. We conclude that, although artificial intelligence is a reality, the scientific production about its application in higher education has not been consolidated.